How Can Ethical Leadership and Emotional Leadership Influence Employees to Quit Intentions? - Sukmayuda, Bagus Caesar; Moeins, Anoesyirwan; Marhalinda, Marhalinda (Kontigensi : Jurnal Ilmiah Manajemen, 2024)
This research aims to determine the mediating effect of interest in the private sector on the relationship between job performance and quitting intentions in companies with an outsourced system, namely manufacturing employees in the packaging sector. This research was conducted in Indonesia from Januari to April 2024 with 140 respondents. The research was a quantitative study using the Structural Equation Model (SEM) method using an analysis tool, namely SmartPLS. This study's results show a relationship between ethical and emotional leadership on employee motivation and job performance. The managerial implication of this research is that if a company wants to create and improve the expected performance, it is necessary to have strong encouragement from the role of ethical and emotional leaders, whereby this will lead to individual behavioural activities that can increase their ability to achieve goals that involve motivation from the encouragement of leadership style.